1987
DOI: 10.1088/0268-1242/2/9/002
|View full text |Cite
|
Sign up to set email alerts
|

A study of the conduction band non-parabolicity, anisotropy and spin splitting in GaAs and InP

Abstract: The conduction bands in GaAs and InP have been studied very accurately through the cyclotron resonance over a wide range of energies using the photoconductive detection technique. Pronounced band non-parabolicity has been measured in GaAs and InP and the band anisotropy has been measured in GaAs.Values for the band-edge masses of 0.0660 mo and 0.07927 mo respectively have been determined. A five-level k e p model of the band structure in the presence of a magnetic field has been used to describe the data where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…The negative sign is assigned from the relation g à ¼ À0:48 þ E F . We determine the factor which reflects the energy dependence of the Landé g-factor to % 5:1 eV À1 for this doping concentration and attribute the deviation from the commonly known factor of 6:3 eV À1 for slightly doped samples [20,21] to bandgap renormalization arising from the high doping concentration. The deviation of g à being a constant is less than 10 À3 T À1 which is at least a factor of 5 lower than for low doped GaAs at low temperatures.…”
mentioning
confidence: 99%
“…The negative sign is assigned from the relation g à ¼ À0:48 þ E F . We determine the factor which reflects the energy dependence of the Landé g-factor to % 5:1 eV À1 for this doping concentration and attribute the deviation from the commonly known factor of 6:3 eV À1 for slightly doped samples [20,21] to bandgap renormalization arising from the high doping concentration. The deviation of g à being a constant is less than 10 À3 T À1 which is at least a factor of 5 lower than for low doped GaAs at low temperatures.…”
mentioning
confidence: 99%
“…Nowadays, five and more band k · p models are state of the art and many lowtemperature experiments have confirmed the incredible accuracy of k · p calculations. [3][4][5][6][7][8] All these experiments support the validity of k · p theory whereas a single but central experiment, which measures the temperature dependence of the electron Landé g factor in GaAs, shows a strong discrepancy between experiment and k · p theory. …”
mentioning
confidence: 75%
“…Nowadays, five and more band k · p models are state of the art and many lowtemperature experiments have confirmed the incredible accuracy of k · p calculations. [3][4][5][6][7][8] All these experiments support the validity of k · p theory whereas a single but central experiment, which measures the temperature dependence of the electron Landé g factor in GaAs, shows a strong discrepancy between experiment and k · p theory. 9 In this Brief Report we present extremely high precision, temperature-dependent measurements of the electron Landé g factor and show that by introducing a temperaturedependent interband matrix element yields a consistent explanation for the temperature dependence of the electron Landé g factor and the effective mass within common k · p theory, while keeping full temperature dependence on the very well-known interband critical points.…”
mentioning
confidence: 75%
“…The Dresselhaus parameter, on the other hand, exhibits an oscillating behavior. In particular, it has been experimentally observed that both the energy gap E 0 (Lautenschlager et al, 1987) and the effective mass m * (Hazama et al, 1986;Hopkins et al, 1987) in systems such as GaAs decrease when the temperature increases. Consequently, we can expect from our qualitative analysis an increase of the Bychkov-Rashba parameter with the temperature.…”
Section: Parametermentioning
confidence: 99%